2020
DOI: 10.37796/2211-8039.1003
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating co-occurrence of depression and sexual dysfunction and related factors among Iranian rural women: a population-based study

Abstract: Background and objectives: Sexual dysfunction and mood disorders have a high prevalence rate and their co-occurrence has been reported in previous studies. This study aimed to determine the prevalence of co-occurrence of sexual dysfunction and depression and related factors in women. Materials and methods: This descriptive-analytical study was carried out on 826 married rural women aged 15e49 years in Sari, Iran in 2018, selected by random sampling. The participants filled the demographic and fertility questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Bakhshi et al [ 24 ] also found a negative relationship between depression and sexual satisfaction among Iranian couples. Khademi et al [ 25 ] reported that women who suffered from mild to severe levels of depression exhibited sexual dysfunction. Thus, one of the major negative consequences of depression could be an increase of sexual dissatisfaction, which is assumed to be a factor for the increasing rate of divorce [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bakhshi et al [ 24 ] also found a negative relationship between depression and sexual satisfaction among Iranian couples. Khademi et al [ 25 ] reported that women who suffered from mild to severe levels of depression exhibited sexual dysfunction. Thus, one of the major negative consequences of depression could be an increase of sexual dissatisfaction, which is assumed to be a factor for the increasing rate of divorce [ 26 ].…”
Section: Introductionmentioning
confidence: 99%